The Effect of Dual Tasks on the Kinematic Pattern and Kinetics of the Lower Extremities in Athletes: A Narrative Review - Majid Hamoongard; Malihe Hadadnezhad (Vesnu Publications, 2020)
Introduction: Anterior cruciate ligament (ACL) injury occurs in sports that require rotational and shear movements. Dual tasks during sports maneuvers increase the risk of injuries. The aim of this study was to systematically review the effect of dual tasks on the kinematics and kinetics of the lower extremities in athletes.Materials and Methods: Articles published between 2000 and 2021 were searched using Google Scholar, and PubMed, Magiran, IranDoc, SPORTDiscus, Institute for Scientific Information (ISI), PEDro, and Scopus databases using a combination of keywords "Biomechanics", "Landing", "Dual task", "Anterior cruciate ligament", "Divided attention", "Decision-making", "Kinetics", and "Kinematics". A total of 58 articles were found. After the exclusion of non-English and non-Persian articles and those with damaged samples, 12 articles were reviewed in this study in full text.Results: In all studies, dual tasks or divided attention were used during jumping, shear, and landing movements, but the type of cognitive and motor interventions and measured variables was different. Adding a secondary task to the movements associated with jumping and landing significantly increased the ground reaction force and dynamic knee valgus (DKV), and reduced hip and knee flexion, which can ultimately increase the risk of ACL injury.Conclusion: Doing injury prevention exercises with cognitive tasks at the same time may cause variability in the central nervous system (CNS) and reduce the incidence of kinematic and kinetic patterns associated with ACL injury.